Aktivitas Farmakologis Ekstrak Kulit Batang dan Buah Garcinia mangostana L. terhadap Percepatan Penyembuhan Luka Sayat pada Mencit (Mus musculus) - Abdul M Ukratalo; Martha Kaihena; Efraim Samson (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Wounds are damage to body tissues caused by various factors, both external and internal, which can disrupt the normal function of these tissues. Many studies have focused on using natural ingredients as adjunctive therapy to accelerate wound healing. One plant that shows therapeutic potential is Garcinia mangostana L. This study aims to assess the therapeutic potential of Garcinia mangostana L. stem bark and fruit peel extracts in accelerating the healing of mice (Mus musculus) incision wounds. The study used a completely randomized design (CRD) with six treatments and three replicates, namely negative control mice (K-), positive control (K+), groups of mice given fruit peel and stem bark extracts of G. mangostana concentrations of 25, 50, 75 and 100%. All mice were cut with a wound diameter of 1 cm. The wounds were then left for 13 days with an interval of 3 days for measurement. The results showed that the administration of G. mangostana fruit peel and stem bark extracts had an effect in accelerating the healing of mice incision wounds. From these results, Garcinia mangostana L. has the potential as an additional therapy in accelerating wound healing in mice, which can be used as a basis for further research related to its application in humans.